2019
DOI: 10.1002/mc.22982
|View full text |Cite
|
Sign up to set email alerts
|

NEK5 promotes breast cancer cell proliferation through up‐regulation of Cyclin A2

Abstract: NEK5, a contraction of NIMA Related Kinase 5, has been shown to regulate the centrosome integrity of cells though; it has been little described in cancer. Herein, to explore the clinicopathological meaning of NEK5 expression in breast cancer, immunohistochemistry was performed to detect the expression of NEK5 on tissue blocks, totaling 203 cases. Quantitative real‐time PCR (qRT‐PCR) was used to evaluate NEK5 mRNA expression with 30 cases of fresh tissues. To observe the function of NEK5 in the growth of breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…promotes the cell cycle G1/S and G2/M transitions [48]. In breast cancer, NEK5-dependent CCNA2 overexpression promotes the proliferation of tumour cells [49]. Moreover, CCNA2 had significant predictive value for the prognosis of ER+ breast cancer patients as well as tamoxifen resistance [50].…”
Section: Discussionmentioning
confidence: 99%
“…promotes the cell cycle G1/S and G2/M transitions [48]. In breast cancer, NEK5-dependent CCNA2 overexpression promotes the proliferation of tumour cells [49]. Moreover, CCNA2 had significant predictive value for the prognosis of ER+ breast cancer patients as well as tamoxifen resistance [50].…”
Section: Discussionmentioning
confidence: 99%
“…Different groups have studied each member of this protein family separately and have observed that the expression of many of them is altered in cancers tissues. The expression of NEK2, NEK6, and NEK11 were related to colorectal cancer [30,[38][39][40], NEK2, NEK3, NEK5, NEK6, and NEK8 to breast cancer [11,[41][42][43][44][45], and NEK2 and NEK6 to prostate cancer [16,46].…”
Section: Discussionmentioning
confidence: 96%
“…Upregulation of NEK5 expression in breast cancer cells promoted tumor progression and silencing of NEK5 suppressed proliferation and inhibited migration and invasion. This important study demonstrated an integral role for NEK5 in cell proliferation and migration pathways in breast cancer through regulation of Cyclin A2 function [27].…”
Section: Introductionmentioning
confidence: 85%